2016
DOI: 10.3390/nano6040065
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Gd-Functionalized Gold Nanoclusters as Potential MRI/CT Contrast Agents

Abstract: Multi-modal imaging plays a key role in the earlier detection of disease. In this work, a facile bioinspired method was developed to synthesize Gd-functionalized gold nanoclusters (Gd-Au NCs). The Gd-Au NCs exhibit a uniform size, with an average size of 5.6 nm in dynamic light scattering (DLS), which is a bit bigger than gold clusters (3.74 nm, DLS), while the fluorescent properties of Gd-Au NCs are almost the same as that of Au NCs. Moreover, the Gd-Au NCs exhibit a high longitudinal relaxivity value (r1) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 31 publications
0
30
0
Order By: Relevance
“…This is indicative that R1 signal increase is as a result of the formation of Gd-based nanoparticles. The boost occurred as a result of the shortening of the longitudinal relaxation time (T1) [ 40 , 41 ] due higher surface area to volume ratio of AuNPs coated on the surface of the nanoparticles, which improves water solubility [ 41 ] and molecule movement, and proton exchange within the /LDH lattice [ 42 , 43 ]. The phenomenon is suspected to be connected with the change in structure of the nanohybrid after AuNPs surface coating, as observed in the GAGZAu TEM and FESEM micrographs.…”
Section: Resultsmentioning
confidence: 99%
“…This is indicative that R1 signal increase is as a result of the formation of Gd-based nanoparticles. The boost occurred as a result of the shortening of the longitudinal relaxation time (T1) [ 40 , 41 ] due higher surface area to volume ratio of AuNPs coated on the surface of the nanoparticles, which improves water solubility [ 41 ] and molecule movement, and proton exchange within the /LDH lattice [ 42 , 43 ]. The phenomenon is suspected to be connected with the change in structure of the nanohybrid after AuNPs surface coating, as observed in the GAGZAu TEM and FESEM micrographs.…”
Section: Resultsmentioning
confidence: 99%
“…Results indicated that there was no significant cytotoxicity (cell viability .80%) for Gd-Au NCs against both COLO-357 ( Figure 3A) and 293T cells ( Figure 3B) at all the concentrations tested, which was consistent with our previously published results. 28 For Gd-Au-NC-GPC-1, no significant cytotoxicity was observed in 293T cells at all concentrations tested, which was similar to Gd-Au NCs ( Figure 3B). However, Gd-Au-NC-GPC-1 showed dose-dependent cytotoxicity (cell viability: from 75.7% to 37.4%) against COLO-357 cells at relatively high concentrations (concentrations: from 30 to 150 mg/L; Figure 3A), which may be associated with complement-dependent cytotoxicity.…”
Section: Cell Toxicity Of Gd-au-nc-gpc-1mentioning
confidence: 55%
“…Gd-Au NCs were prepared according to the methods previously reported by our group. 28 BSA, commonly employed as a substrate for biomineralization, was selected as the model protein for this study. Upon adding HAuCl 4 and GdCl 3 to the aqueous BSA solution, the protein molecules sequestered and entrapped Au and Gd ions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past decades, gold (Au) nanostructures have received widespread research interests, due to their fascinating size- and shape-dependent physicochemical properties [ 1 , 2 , 3 , 4 , 5 , 6 ], and their various promising applications in catalysis [ 7 , 8 ], chemical sensing [ 9 , 10 , 11 , 12 ], plasmonics [ 13 ], and surface-enhanced Raman scattering (SERS) [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. In order to tune their unique properties and further improve their performance, Au nanostructures with diverse geometric features, including plate [ 23 ], cube [ 24 ], cage [ 25 ], wire [ 26 ], sphere [ 27 ], decahedron [ 28 ], and branched nanostructures [ 29 ] have been synthesized through a rich variety of chemical methods.…”
Section: Introductionmentioning
confidence: 99%